An AAV vaccine targeting the RBD of the SARS-CoV-2 S protein induces effective neutralizing antibody titers in mice and canines. Issue 9 (23rd February 2022) - Liu, Fei; Feng, Canbin; Xu, Shiqi; Wu, Qiang; Tang, Jian; Chen, Yan; Xu, Ruisheng; Chen, Fuliang; Gao, Ni; Xu, Zhengzheng; Gu, Shihui; Lan, Yang; et al.
Highlights: AAV based-vaccine could efficiently mediate the RBD protein expression of the SARS-CoV-2 in mammalian cells. AAV based-vaccine could rapidly induce strong immune responses in mice, which maintaining at least six months. AAV-3xRBD vaccine could elicit the high level of neutralizing antibodies against SARS-CoV-2 in mice. AAV-3xRBD vaccine has the ability of inducing the specific antibodies against SARS-CoV-2 in canines. Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has resulted in catastrophic damage worldwide. Accordingly, the development of powerful, safe, easily accessible vaccines with long-term effectiveness is understood as an urgently needed countermeasure against this ongoing pandemic. Guided by this strong promise of using AAVs, we here designed, optimized, and developed an AAV-based vaccines (including AAV-RBD(max), AAV-RBD(wt), AAV-2xRBD, and AAV-3xRBD) that elicit strong immune responses against the RBD domain of the SARS-CoV-2 S protein. These immunogenic responses have proven long-lived, with near peak levels for at least six months in mice. Notably, the sera immunized with AAV-3xRBD vaccine contains powerful neutralizing antibodies against the SARS-CoV-2 pseudovirus. Further evidence proven that potent specific antibodies could also be elicited in canines after vaccination with AAV-3xRBD vaccine.